Left Atrial Functional Remodeling in Lone Atrial Fibrillation: A Two‐Dimensional Speckle Tracking Echocardiographic Study. Issue 9 (5th April 2013) - Hong, Jin; Gu, Xiaoyan; An, Ping; Luo, Taiyang; Lv, Qiang; Kang, Junping; He, Yihua; Hu, Rong; Liu, Xiaohui; Ma, Changsheng
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to assess left atrial (LA) functional remodeling in lone atrial fibrillation (LAF) patients via two‐dimensional speckle tracking echocardiography (2DSTE). Methods Forty‐five paroxysmal LAF patients and 30 healthy controls underwent 2DSTE in sinus rhythm. Longitudinal LA strain/strain rate (LAS/LASR) of booster, reservoir, and conduit function in apical four‐ and two‐chamber views were measured and averages of the 2 views were used. Results The 2 groups had similarity in LA volume. LAS and LASR of the 3 phasic functions were reduced in patients. Comparing the 2 groups, LA booster strain (LASa) and strain rate were −12.31 ± 3.15 versus −15.30 ± 2.52% and −1.64 ± 0.51 versus −2.08 ± 0.48 1/sec, respectively, P < 0.05 for both. Multivariate regression confirmed that LAF was an independent determinant of LAS/LASR reduction. LASa was the most accurate parameter for differentiating LAF patients from controls (area under receiver operating characteristic curve, 0.763; cutoff value, −14.3%; sensitivity, 71.1% and specificity, 70.0%). Finally, LASa decrement was found to be the only significant predictor of early atrial fibrillation (AF) recurrence (odds ratio [OR], 1.39 per unit decrement; 95% CI, 1.02–1.89; P = 0.038). Conclusions Remodeling of LA booster pump, reservoir, and conduit function in LAF patients can be detected by 2DSTE before structural remodeling. Occurrence of LAF is associated with impairment of LA intrinsic myocardial properties. LASa can differentiate LAF patients and lower LASa is associated with early recurrence of AF after ablation.